The Global Social Enterprise Lawmaking Phenomenon: State Initiatives on Purpose, Capital, and Taxation - Liao, Carol; Tawfik, Elsir U.; Teichreb, Pat (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2019)
New laws designed to foster and govern social enterprises are propagating throughout the world. Beyond American initiatives, relatively little has been written to date on the global contagion of lawmaking to address the burgeoning field of social enterprise. Increased corporate lobbying to transplant American “benefit” corporation legislation into other countries, with little sensitivity towards existing legal ecosystems in those nations, has generated an urgency to broaden the literature and unearth the wide range of social enterprise law initiatives occurring across the globe. This article identifies over 40 state initiatives across 30 countries to distinguish this international movement. Critical thematic issues are identified from the available data, in hopes of shifting the focus away from private American interests in non-US countries and adding new knowledge to the development of social enterprise law and policies in the years ahead. This article begins by detailing various ways in which states have defined the purpose of social enterprise and social enterprise-type businesses, including how jurisdictions have experimented between state-run certifications and separate corporate legal structures to meet growing demands from particular sectors and stakeholders. We find that most jurisdictions require social enterprises to have a specific social purpose designed to serve the targeted needs of specific sectors, marginalized groups, and/or vulnerable communities. Next, we examine how new state legislation has sought to ease or restrict capital access for these social enterprises. Finally, we provide a detailed overview of various tax initiatives explored by states to promote and foster social enterprises. We suggest that lawmakers proceed with caution in the development of social enterprise laws, particularly when they are in response to private interest groups, and engage in fulsome discussions on the range of available legal methods to foster social enterprise within their jurisdictions.